2018
DOI: 10.2147/ppa.s167508
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence and persistence in patients with rheumatoid arthritis, psoriasis, and psoriatic arthritis: a systematic literature review

Abstract: PurposeProper adherence and persistence to medications are crucial for better quality of life and improved outcomes in rheumatoid arthritis (RA), psoriasis (PsO), and psoriatic arthritis (PsA). We systematically describe current adherence and persistence patterns for RA, PsO, and PsA, with a focus on biologics and identifying factors associated with adherence and persistence.Patients and methodsUsing various databases, a systematic literature review of US-based studies published from 2000 to 2015 on medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
103
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 54 publications
8
103
0
3
Order By: Relevance
“…Also, quicker efficacy could lead to increased patient compliance. In another recent study, the lack of efficacy was the most common reason why patients with psoriasis discontinued a biologic treatment …”
mentioning
confidence: 99%
“…Also, quicker efficacy could lead to increased patient compliance. In another recent study, the lack of efficacy was the most common reason why patients with psoriasis discontinued a biologic treatment …”
mentioning
confidence: 99%
“…10 A systemic review showed that the median adherence rate for etanercept was 63% (range, 16-73%) in patients with rheumatoid arthritis. 11 Low adherence to therapeutic regimen has negative consequences and can lead to substantial costs, increased disease flares, disease progression, increased disability, additional medical therapy, and sometimes surgery. 12,13 Nonadherence can be intentional and nonintentional, and poor manual dexterity can impact the person's ability and skill at medicine-taking leading to unintentional nonadherence.…”
Section: Introductionmentioning
confidence: 99%
“…Safety, pharmacodynamics and efficacy can only be adequately assessed and interpreted if patient data on treatment adherence are available. The impact of poor adherence varies across numerous chronic skin disorders . For instance, non‐adherence to topical regimens leads to increased scores on the six area, six sign atopic dermatitis (SASSAD) severity scale, indicating the disease severity in patients with atopic dermatitis .…”
Section: Introductionmentioning
confidence: 99%
“…The impact of poor adherence varies across numerous chronic skin disorders. 9,10 For instance, non-adherence to topical regimens leads to increased scores on the six area, six sign atopic dermatitis (SASSAD) severity scale, indicating the disease severity in patients with atopic dermatitis. 11 For this reason, increasing adherence may even have a larger impact on patient-reported outcomes than the improvement of the treatment itself.…”
Section: Introductionmentioning
confidence: 99%